Perception of Patient Regarding Nurse Patient Communication Barrier: A Case of Chitwan Medical College, Chitwan - Dhungana, Gita; Thulung, Bedantakala; Mani Dhungana, Surya (International Journal of Nursing Research, 2023)
Aim and Objective: Nurse patient communication is one of the important factors in providing an effective and quality nursing care and services. The objective of the study was to assess the level of nurse-patient communication barriers as perceived by patient at teaching hospital. Methods: The study has followed the quantitative descriptive cross-sectional design and has used the – semi structured interview schedule along with Likert rating scale ranging from five to one. Complete enumeration technique was used. Total patients 201 were selected from general wards having at least 3 days hospital stay. The study has utilized the data analysis tools such as EpiData, SPSS version 21 to analyze the information using descriptive and inferential statistics. They are common factors, nurse related factors, patients related factors, and environment-related factors. Results: The study revealed that more than 50% of patients were male with the average 40.64 ± 14.75. About 78.10% of patients told that most barriers during nurse-patients communication. Among four factors patient related factors (3.77 ± 0.55), nurse related barrier (3.29 ± 0.59), environmental barrier (3.12 ± 0.23), and common barrier (2.73 ± 0.79) were the most and least important factors, respectively. Language difference (mean score 3.38), inadequate explanation about procedure or treatment by nurse (mean score 4.07), and among them hearing problems (mean score 4.81), noisy environment (mean score 4.09) were major barrier subfactors while communication between patient and nurse. Conclusion: It is concluded that the majority of patients had perceived level of barriers in overall as most barriers. Finally, the study has recommended that in-service education, effective supervision and reinforcement scheme, development, and utilization of guidelines for nurse-patients communication.